Association between high-sensitivity cardiac troponin T and future cardiovascular incidence in a general Japanese population: results from the Tohoku medical megabank project. (18th August 2019) - Takahashi, Yuji; Satoh, Mamoru; Ohmomo, Hideki; Tanaka, Fumitaka; Osaki, Takuya; Tanno, Kozo; Nasu, Takahito; Sakata, Kiyomi; Morino, Yoshihiro; Sobue, Kenji; Sasaki, Makoto
Abstract: Purpose: Elevation of high-sensitivity cardiac troponin T (hs-cTnT) is associated with an increased risk of cardiovascular disease (CVD). This study determined whether hs-cTnT was detectable with N-terminal pro-b-type natriuretic peptide (NT-proBNP) and related to CV risk factors in a general Japanese population. Materials and methods: The Tohoku Medical Megabank Organization pooled individual participant data for a population-based cohort study in the Iwate prefecture ( n = 30, 193, age = 60.2 ± 11.5 year). Results: Hs-cTnT levels were higher in participants with hypertension, diabetes mellitus than in participants without these conditions (all p s < 0.001). Logistic regression analysis demonstrated that NT-proBNP was strongly associated with elevation of hs-cTnT (OR = 3.35, 95% CI = 2.90–3.89, p < 0.001). The receiver operating characteristic curve analysis showed that hs-cTnT was one of useful biomarker for the differentiation of high risk for CVD (the Suita score ≥ 56) from a general population. Logistic regression analysis demonstrated hs-cTnT levels were related to the CVD high risk group (OR = 2.67, 95% CI = 2.28–3.14, p < 0.001). Conclusions: Hs-cTnT levels are associated with elevation of NT-proBNP and high Suita score, which suggests that elevated hs-cTnT is related to subclinical myocardial damage and indicates CV risk.